Analysis of The Application of Multicultural Education in Islamic Schools Based on Islamic Boarding Schools - Wening Purbatin Palupi Soenjoto; Dwi Runjani Juwita (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
Multicultural education is a bridge in achieving the common life of humankind from various cultures in a global era full of new challenges. Intercultural meetings can have the potential to benefit but at the same time cause misunderstanding. Educational equality, and dedication become the foundation of multicultural education in the educational experience so that all students can realize all their full potential and make them aware of people who are aware and active locally, nationally and globally. The culture of Islamic boarding school is an activity that is applied by the kyai and is adhered to by the students as well as being a characteristic tailored to the policy of the Islamic boarding school. based on a library search for analyzing the application of multicultural education in Islamic boarding schools based on interviews with clerics, teachers and students to get valid data. The method used in this study is a qualitative method with descriptive analysis. The research subjects were 150 students, aged 15-19 years who provided research data through interviews, surveys and documentation with triangulation data processing to obtain valid research results.